Experiences of nurses and patients with the implementation of the CCMDD programme - Ragosebo P. Sekopa; Robert T. Netangaheni (African Journal of Primary Health Care & Family Medicine)
Background: The Central Chronic Medicines Dispensing and Distribution (CCMDD) programme has good benefits for both patients with chronic conditions and nurses if it is effectively implemented. In most of the Sekhukhune Primary Health Care (PHC) facilities, the implementation of the CCMDD programme has been highly challenging but at the same time very beneficial.